An extended application of β-Ga2O3 single crystals to the laser field: Cr4+:β-Ga2O3 utilized as a new promising saturable absorber. Issue 35 (19th April 2017) - Mu, Wenxiang; Yin, Yanru; Jia, Zhitai; Wang, Lijuan; Sun, Jie; Wang, Mengxia; Tang, Cheng; Hu, Qiangqiang; Gao, Zeliang; Zhang, Jian; Lin, Na; Veronesi, Stefano; et al.
Abstract : A Cr 4+ -doped β-Ga2 O3 crystal has been grown successfully and demonstrated as a saturable absorber for the first time. Abstract : Considering their easy growth and doping in bulk crystal growth, and good crystalline quality, β-Ga2 O3 single crystals, a very important wide-bandgap semiconductor, are now also considered to be a promising optical crystal candidate. In this work, a Cr 4+ :β-Ga2 O3 single crystal has been grown successfully by the edge-defined film-fed growth method. The thermal conductivity of Cr 4+ :β-Ga2 O3 has been measured along the a * direction at room temperature obtaining 16.2 W m −1 K −1, and it was much larger than that of the usually used Cr 4+ -doped crystals, such as Y3 Al5 O12 (YAG) or YVO4 . The Raman spectrum indicated that the cutoff phonon energy of the β-Ga2 O3 crystal was 767.8 cm −1 . A passively Q-switched nanosecond pulsed Nd:YAG laser based on a Cr 4+ :β-Ga2 O3 saturable absorber was experimentally demonstrated for the first time to our knowledge and its mechanism is explained by first-principles calculations. By inserting the Cr 4+ :β-Ga2 O3 crystal into the Nd:YAG laser cavity, a Q-switched laser operation was obtained with a maximum average output power of 50 mW. The corresponding pulse repetition rate, pulse width, and pulse energy were determined to be of 421.5 kHz, 235.2 ns and 0.12 μJ, respectively.